Effects of growing environment, genotype, and commercial fertilization levels on free asparagine concentration in Western Canadian wheat. Issue 1 (18th November 2020) - Xie, Yi; Malunga, Lovemore Nkhata; Ames, Nancy P.; Waterer, John; Khorshidi, Ali Salimi; Scanlon, Martin G.
Abstract: Background and objectives: Free asparagine (ASN) is the precursor to the formation of acrylamide, which is a probable neurotoxic and carcinogenic compound formed during high‐temperature (>120°C) processing of starchy foods, such as cereal‐based products. Controlling the acrylamide concentration of cereal‐based products, for example, bread, within the allowable levels established by the European Commission, is necessary for food safety purposes. One effective measure recommended by the European Commission to mitigate acrylamide in cereal‐based products is to reduce free ASN levels in raw ingredients, for example, wheat. Therefore, knowledge of free ASN levels in Canadian commercial wheat and the strategies to reduce its formation is necessary for the Canadian wheat industry to secure global market access for Canadian wheat. The objective of this study was to understand the effects of genotype, growing environment, and fertilization on free ASN concentration of whole‐wheat flour from Western Canadian wheat varieties. Findings: The free ASN concentration of whole‐wheat flours in this study ranged from 281 to 1, 014 µg/g (dry basis). The variation in free ASN levels in wheat was mainly influenced by the growing environment (44%), followed by genotype (31%) and the interaction between genotype and environment (18%). Although being significant, the effects of fertilization and interactions involving fertilization on free ASN concentration in whole‐wheat flour were minimal (0.7%–2.2%). Conclusion: Growing wheat genotypes in suitable environments, along with the selection of wheat genotypes with lower potential for free ASN formation, are the most effective strategies to control free ASN levels in Canadian wheat. Significance and novelty: Limited knowledge in regard to free ASN concentration and the strategies to reduce its formation in Canadian wheat may have a serious impact on Canadian wheat access to global markets, especially the European market. This study provides an understanding of the effects of growing environment, genotype, and fertilization on free ASN concentration of select Western Canadian commercial wheat varieties.